FIKSATOR UNTUK PEWARNA ALAMI (Natural Dyes Fixator) - Yasmi Teni Susiati; Enggar Kartikasari (Universitas Sarjanawiyata Tamansiswa, 2017)
Natural dyes has a feature to produce soft colors. One of the natural dyes that can be used is pinang extract which applied to the jumputan textile. This research generally try to discover the effectiveness of pinang extracts for textiles coloring in terms of color fading endurance against the washing using whiting fixator and gambir. The research was conducted in PKK FKIP UST laboratory. The research population was: textiles, pinang extract, whiting and gambir. The research samples : textiles, pinang extract, whiting and gambir with the two treatments, the 10% and 20% concentration. This research using experimental methods and then tested in the Laboratorium Balai Batik. The assessment results of Indonesian National Standard (SNI) is grey scale. Visually, the result produced light brown color without the fixator, while using the whiting fixator produced a dark brown color and gambir produced yellowish brown color. Whiting fixator better than gambir because it produce sharper colors and has a higher value of color change.